Taints and off-flavours in food - Baigrie, Brian (Woodhead Pub. ; CRC Press, 2003)
Taints and off-flavours are a major problem for the food industry. Part 1 of this important collection reviews the major causes of taints and off-flavours, from oxidative rancidity and microbiologically-derived off-flavours, to packaging materials as a source of taints. Part 2 of the book discusses the range of techniques for detecting taints and off-flavours, from sensory analysis to instrumental techniques, including the development of new rapid, on-line sensors.
Keywords: Food contamination.; Flavor.; Food -- Sensory evaluation.; Food -- Analysis.; elektronické knihy; electronic books